Hospital Global Budgeting - Dredge, Robert (World Bank, Washington, DC, 2013)
This paper is a practitioners guide to the introduction of a global budget into a hospital setting based on real World Bank projects in emerging, former soviet countries and in the UK NHS. It traces the steps from a centrally allocated, line item type allocated budget to one that is set on predetermined objective and measurable factors. These are based, where possible, on the health needs of the population served by the hospital. It considers how a global budget can be established and managed to generate local ownership and commitment to its delivery. It deals with incentives for both efficiency and performance. Examples of different contracting regimes, and how they fit into a global budget framework are given. Mechanisms for the periodic revision of the budget for issues such as inflation are given. There are separate notes on how a global budget can fit into a policy regime, how to cost services, and how to arrange contract for individual services. There are also suggestions on how to fund special payments that may vary from year to year, such as capital, research and development and Training and Education.